Цукор і бурякоцукрове виробництво: історія виникнення і становлення - Філоненко, С.В. (Питання історії науки і техніки, 2008)
Освещено значение сахара для человеческого организма, история его извлечения из
различных сахароносов. Рассмотрен исторический путь распространения сахарного
тростника как первой промышленной сахарной культуры и сахарной свеклы – альтернативного сахароноса стран с умеренным климатом. The meaning of sugar for a human body, history of its extraction from various sugar
plants are considered. The historical way of distribution of a sugar cane as first industrial
sugar culture and sugar beet is considered? An alternative sugar plant of the countries with a
temperate climate.